Ultrasonographic Evaluation of Maxillofacial Swelling in a Pediatric Patient with Xeroderma Pigmentosum - Görürgöz Cansu; Sakalli Nilsu; Kul Ferah Mutlu; Özalp Nurhan Uslu (Balkan Stomatological Society, 2019)
Background/Aim: Xeroderma pigmentosum (XP) is an autosomal recessive skin disease. Affected patients have skin problems, oral mucosa and neurologic symptoms. In these patients, erythematous, hyperpigmented or malignant skin lesions may occur in the sun-exposed areas. Leukoplakia, erythroplakia, and squamous cell carcinoma of the tip of the tongue and lips are common oral lesions associated with XP.